(untitled) (Ameghiniana, 2013)
Several Nothofagidites species (fossil grains of Nothofagus) have been described from Tertiary and Cretaceous sediments of a bore located in Tierra de! Fuego aproximately 14 kilometers south of the San Sebastian bay in Estancia La Sara. The first record of fossil pollen grains of Nothofagus be!ong to the Upper Cretaceous sediments at 1607 m depth, The described species of the Nothofagus "fusca group" are: Nothofagidites d. uiaipatoensis Couper, N. rocaensis Romero and two new species N. saraensis and N. fortispinulosus, of the "menziesi group". N. suggatei and N. asperus and of the "brassi group" N. kaitangatus TePunga, N. cranuiellae Couper, N. dorotensis Romero, N. uisserensis Romero, and five new species: N. fuegiensis, N. paucispinulosus, N. anisoechinatus, N. acromegacantbus and N. bystricospberoides.